Implikasi Hukum Ketenagakerjaan terhadap Hubungan Industrial di Era Globalisasi - Fathanudien, Anthon (Wajah Hukum, 2025)
The era of globalization has brought significant changes in the structure and dynamics of industrial relations in various countries, including Indonesia. These changes include the liberalization of the labor market, the entry of foreign investment, and the adoption of new technologies and work systems that demand high flexibility in employment relations. This condition gives rise to various complex employment law implications, both in terms of labor protection, contractual flexibility, and the role of trade unions. This study aims to analyze how the Indonesian labor law system responds to the challenges of globalization in maintaining a balance between the interests of workers and employers and ensuring the stability of industrial relations. A normative legal approach is used by examining national laws and regulations, international conventions, and contemporary industrial relations practices. The results of the study show that there is still a gap between labor law norms and the reality in the field, especially regarding the issues of flexible employment, outsourcing, digitalization of the workforce, and protection of basic workers' rights. Therefore, it is necessary to reformulate employment policies that are adaptive, equitable, and oriented towards the development of harmonious and sustainable industrial relations in the global era.